PENGARUH MICROWAVE HEATING TERHADAP KUALITAS MINYAK DEDAK PADI - Rahkadima, Yulia Tri; Fitri, Medya Ayunda (Journal of Research and Technology, 2018)
Rice bran oil as an alternative edible oil is promising to be developed. However, the presence of lipaze enzym which hydrolyze actively trigliceride into free fatty acid results rice bran quality can not be controlled and tend to degrade. Stabilization proccess was needed to overcome this isue. Stabilization with microwave heating has been carried out to study the effect of stabilization toward the quality of rice bran oil. The results showed that the highest percentage of oil mass 7.67% was obtained at medium power (power 2), stabilization time 1 minute and the extraction waiting time for 0 week. Meanwhile, the levels of free fatty acids tended to be constant when the proccess was carried out at power 3 (high power) for all stabilization times. Microwave heating was effective enough to reduce the lipase enzyme in rice bran so as free fatty acid content did not increase significantly.